Sociología sistémica de lo político. Lineamientos de un programa de investigación - Estrada Saavedra, Marco (El Colegio de México, 2018)
In this article we present an outline of a systemic sociology of the political in development. We start from the problematization of the political dimensions of collective action and social movements as conventionally understood by corresponding medium scope theories. Before the simplifications of these theories, we explore the possibility of making our understanding of the phenomenon more complex by reviewing contemporary discussions around the political in contemporary political philosophy. However, a concept of the political, coming from philosophy must be reformulated to make it suitable for social sciences empirical research. A promising way to achieve this aim is to integrate it into the description of the political system as its counterpart and reformulate it according to conceptual grammar of Niklas Luhmann's theory of social systems. The gain in abstraction and generalization of the political obtained in this way is also enriched with the methodological contributions of the so-called anthropology of the State. The systemic sociology of the political is proposed as a conceptual and analytical model that helps for empirical research and the apprehension of the sociohistorical differences of the political and the complex and conflictive relations between State and society in societies such as Latin American ones.